Adoption of Critical Information Literacy methods of teaching in selected University Libraries in Kenya - Njue Mutegi, James; Oyieke, Lilian; Mbenge Ndiku, Tabitha (International Journal of Knowledge Content Development & Technology, 2025)
This study investigated the adoption of Critical Information Literacy (CIL) methods of teaching in selected university libraries in Kenya. CIL examines effectiveness of Information Literacy (IL), disrupts inequitable systems, and creates student-driven IL instruction. This study adopted Mixed Research Methods (MRD) encompassing qualitative and quantitative approaches in form of a convergent parallel research design. The researcher used purposeful sampling by adapting an inclusion and exclusion criteria table to identify the universities, students, reference and ICT librarians that qualified for this study. The population of the study consisted of 473 respondents comprising 376 undergraduate and postgraduate students from Information Science, 14 reference/ICT librarians and 14 university librarians. The study established that the selected university libraries offered a range of CIL methods such as lecture method, virtual and orientation. The limitations of methods used in teaching CIL were that they were not interesting or motivating, did not involve critical thinking skills, lacked active learning techniques and failed to encourage the acquisition of practical skills strategies included allocation of more time for teaching CIL, sensitizing students on value of CIL, providing more ICT resources, use of interesting and clear examples.